Modélisation Du Cycle Des Roches Sédimentaires Au Profit Des Apprenants De La Première Année Collégiale - Tajdi, Amina; Nazih, Ali; Eddif, Atika; Kenafi, Jamila; Mahboubi, Issam; Oubezza, Jihad; Chelouati, Et Tarik (European Scientific Journal, ESJ, 2017)
The present study aims to identify the difficulties to assimilate the concept of the sedimentary rocks cycle for first year middle high school students. It also aims to test the importance of a physical model that we have proposed. In order to collect the didactic difficulties encountered in the classroom as well as the means suggested to overcome them, we administered an anonymous questionnaire to 44 teachers of Life and Earth Sciences. To test the significance of the model, 184 learners were divided into two groups. While the first group was taught using a model, no specific one was used to teach the other group. After a constructive evaluation, 73% of the learners in the first group achieved satisfactory results, against 34% in the second one.